2011
DOI: 10.1002/hfm.20263
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of managers' and safety delegates' perceptions of work environment priorities in the manufacturing industry

Abstract: This study investigated the attention and priority accorded to factors of work environment within manufacturing companies, as perceived by managers and safety delegates at small-and medium-sized enterprises. Representatives from 142 Swedish manufacturing companies answered a 43-item questionnaire covering seven areas of the work environment and a priority-ranking question of company interests. Respondents (n = 249) rated the present situation and the situation one year earlier, using a visual analogue scale. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…No existing instrument was judged as satisfactory to use for the study aim. More information on the development of the questionnaire and procedure of the data collection have been described in Nordlöf et al [ 27 ], where the questionnaire is included as an appendix. Prior to data collection the questionnaire was validated in a pilot to adjust for face validity, and the reliability of the index constructs were satisfactory, as checked by Cronbach’s alpha (range: 0.77–0.91).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No existing instrument was judged as satisfactory to use for the study aim. More information on the development of the questionnaire and procedure of the data collection have been described in Nordlöf et al [ 27 ], where the questionnaire is included as an appendix. Prior to data collection the questionnaire was validated in a pilot to adjust for face validity, and the reliability of the index constructs were satisfactory, as checked by Cronbach’s alpha (range: 0.77–0.91).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study [ 27 ] on perceptions of work environment prioritizations demonstrated that those in professional roles within the organization have different views on how much their company prioritizes the work environment, whereby, within the same companies, managers believe that the work environment gets greater priority than the safety delegates believe. The present study analyzes the dataset from that earlier study, in relation to whether company size can be linked to perceptions of work environment prioritizations.…”
Section: Introductionmentioning
confidence: 99%
“…Managers experience the conflict of priorities because of handling different tasks [35]. They perceive conflicts of interest [52].…”
Section: Communication and Cooperationmentioning
confidence: 99%
“…The conclusion pointed out that behavioral interventions are successful in an industry with a high risk of injury. In Reference [3], a study was performed on medium-and small-sized manufacturing companies with regards to work environment factors, as seen by managers and safety delegates. The results show that the perceptions differ significantly between two professional roles.…”
Section: Introductionmentioning
confidence: 99%